Chronic wasting disease of mule deer: transmission and pathogenesis - Sigurdson, Christina Jenny, author (Colorado State University. Libraries, 2001)
Chronic wasting disease (CWD) is a naturally occurring, horizontally transmitted prion disease of deer and elk. Understanding mechanisms and pathways of prion transmucosal entry and subsequent neuroinvasion is critical for development of diagnostic assays and intervention strategies; thus, we have studied CWD of deer as a model for TSE pathogenesis. CWD PrPres (PrPCWD), the abnormal isoform of the prion protein, is abundant in lymphoid tissue of infected deer. Fawns exposed orally to a CWD brain homogenate revealed PrPCWD in regional lymphoid germinal centers (retropharyngeal lymph node, Peyer's patches, and ileocecal lymph node) by 42 days post-exposure—indicating that a substantial lymphoid phase of PrPCWD amplification occurs prior to CNS involvement and clinical disease. This lymphoid tissue phase is similar to vCJD in humans and scrapie in sheep and may reflect the initial pathway of CWD infection in deer. Using tonsil sections dually-labelled for lymphoid cell phenotype markers and PrPCWD, we have identified a population of cells associated with PrPCWD as follicular dendritic cells (FDC), B cells, and tingible body macrophages in the germinal center. PrPCWD appears to colocalize with a cell surface marker indicating that PrP is located on the surface of the FDC, possibly associated with immune complexes or complement receptors. Relatively little is known of the initial prion trafficking pathways to lymphoid tissue or the CNS. We determined that the peripheral nervous system plays a role in CWD prion spread to the CNS. PrPCWD was demonstrated in the myenteric plexus and peripheral nerves, including the vagus nerve which innervates the alimentary tract, as well as the adrenal medulla, pancreatic islet cells, and in the pituitary using IHC. The results of these studies will contribute to understanding PrP trafficking in the lymphoid system and could provide a basis for development of blood-based diagnostic assays and intervention strategies.
Keywords: zoology